Diversidade de fontes de pólen utilizadas por abelhas Centridini em áreas de Cerrado - Rabelo, Laíce Souza (2012)
The native bees are mainly responsible for pollination in natural and agricultural systems. In this context, information about food sources and the patterns of their use by sympatric species can support actions of conservation and management of this group. In this study we presented information about the food niche of Centridini bees in Cerrado areas and the influence of bee s (body size) and plant s (pollen grain size and flower s anther type) morphologies in the similarity of the use of the pollen sources and interactions network structure identified by pollen analyzes. For this we analyzed samples (n= 69) from the scopa of 16 Centridini bee species, that were collected in the period from 2004 to 2011, after visiting West Indian cherry flowers (Malpighia emarginata), and nests of Centris analis (n = 8) and Centris tarsata (n = 8), collected between October and March from 2008 to 2010. The collection of bees visiting the West Indian cherry flowers was held in an orchard at Experimental Station of Água Limpa (ESAL), while the nests were from ESAL and Ecological Station of Panga, both located in Uberlândia, MG. The analysis of scopa samples showed that Centridini bees and the plants used as pollen sources (n= 23) constituted a nested network (NODF= 45.06; per= pce< 0.001) and that the greatest similarity in the use of these sources occurred between C. analis and Centris poecila (81.25%). Additionally, there was predominance of the use of plants with flowers with non-poricidal anthers (U= 255.00, p<0.001) and correlation between body size and the use of pollen from flowers with poricidal anthers (rs= 0.591, 0.01<p<0.02). Analyzes of the cells brood content showed that females used a few plant species as pollen sources (n= 7), and C. analis used mostly Heteropterys spp. (Malpighiacae) (62.31%) and plants with flowers with non-poricidal anthers (U= 54.00, p= 0.015) and C. tarsata used profusely Solanum lycocarpum (Solanaceae) (62.02%) and plants with flowers with poricidal anthers (U= 1.00, p= 0.001). In addition, there was difference in food niche width of these species (t= -17.023, p <0.001, df= 19090), low similarity (20.16%) in the use of the pollen sources and the use of pollen grain of medium size by C. analis and C. tarsata (U= 14.609, p= 0.001 and U= 14.201, p= 0.001). Therefore, considering the results obtained, it can be concluded that Malpighiaceae species were the main pollen and oil sources for Centridini in Cerrado areas, that the larger bees were considered more general in the interactions network and those that had a greater tendency to use pollen sources with poricidal anthers, as well as C. tarsata. Despite C. analis and C. tarsata to be sympatric species, to belong to the same functional group and to present overlap in relation to the nesting period, they used abundantly different pollen sources which suggests the occurrence of partitioning of source between these species.